The Influence of Western European Pictorial Traditions in Arsen Kurbanov’s Paintings - Hamidov, Timur S.; Magomedov, Amirbek J.; Abdullayeva, Elmira B.; Sultanova, Gulizar A.; Shabaeva, Alla K.; Saidova, Angela S. (Journal of History Culture and Art Research, 2018)
This article is devoted to the study of the picturesque heritage of the Dagestan artist Arsen Kurbanov (1990s). The choice of these chronological frames is conditioned by the desire to study the initial period of the artist’s creative work, which determined his further creative path of development, his aesthetic preferences and style affiliation. Arsen Kurbanov’s creative method was significantly developed from the traditions of Western European academic painting. The revival of the Italian Quattrocento era, the peculiarities of the artistic vision of the Northern Renaissance masters, the creativity of Vermeer Delft, served as the basics by which the Dagestani artist was inspired. Creating his compositions, allowing to recall the works of Giotto di Bondone, and the masters of the early Renaissance, as well as P. Brueghel and Vermeer, Arsen Kurbanov does not resort to "blind" copying of their manners and methods of painting, but reinterprets creatively the heritage of great masters. By introducing the elements of identity into his works that go back to the cultural peculiarities of his people - the Dagestani reality, and also developing in the bosom of the Petersburg Academy of Arts, he contributes to the development of his original style, unlike all previous achievements of classical art. Thus, the ancient mythology, and the biblical subjects of his paintings, receive new specific forms of expression in the pluralistic environment of contemporary artistic trends. They acquire the features of relevance and "vitality" in the system of academic art canons. The appeal to historical reminiscences and taking over the best achievements from the pictorial heritage of the masters of the past allowed Arsen Kurbanov to find his place in the newest art of Russia, and to remain a unique, interesting and contemporary artist at the same time. The studying of classical painting tradition role in the development of Arsen Kurbanov’s artistic language is the main goal of the proposed article. A wide spectrum of various means of picturesque expressiveness and artistic techniques is analyzed, which served as a fundamental factor in his aesthetic preferences and recognizable handwriting.